Dialektatlas Mittleres Westdeutschland (DMW) - Methodik, Akquise, Exploration und Analyse - Wallmeier, Nadine; Kuhmichel, Katrin; Gehrke, Gero; Sauermilch, Stephanie (Niederdeutsches Wort)

Messung der Fähigkeit zur Unterrichtsplanung bei Lehramtsstudierenden - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Ursachen für Veränderungen des physikdidaktischen Wissens im Studium - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Basismodelle in Unterrichtsplanungen im Praxissemester Physik - Buschhütter, David; Mutschler, Tanja; Schröder, Jan; Riese, Josef; Borowski, Andreas (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Entwicklung eines Fachpraktikums im Techniklehramt - Ermel, Dorothee; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Wie entwickeln sich Wissen und Fähigkeiten im Physiklehramtsstudium? - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Estimation of acoustic wave non-linearity in ultrasonic measurement systems - Claes, Leander; Steidl, Carolin; Hetkämper, Tim; Henning, Bernd (arXiv.org)

Does Informational Equivalence Preserve Strategic Behavior? Experimental Results on Trockel’s Model of Selten’s Chain Store Story - Duman, Papatya (Games)
The purpose of this study is to experimentally test Trockel’s game, which is a modelling of the classical Chain Store Game (CSG), and determine whether one of the two theories of Equality and Deterrence may better account for the observed behavior. The CSG is an example of a simple game in extensive form where the actual behavior of well-informed players cannot be expected to agree with the clear results of game theoretical reasoning. To explain the disagreement between the theory and the expected behavior, Trockel’s game is proposed as an alternative modelling of the scenario. The existence of more than one equilibrium in Trockel’s game opens a door for reputation building. This study is the first attempt to experimentally test this alternative game with the same purpose. According to my data, there is some evidence in favor of both Equality and Deterrence Hypotheses. However, since the strategies compatible with the Equality Hypothesis are played more frequently, I observe some patterns which share the same intuition with the Deterrence Hypothesis.
Keywords: Applied Mathematics; Statistics; Probability and Uncertainty; Statistics and Probability

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Frühe alltagsintegrierte mathematische Bildung. Eine Einleitung - Bruns, Julia; Vogtländer, A. (Frühe alltagsintegrierte mathematische Bildung. Handreichung für Lehrende)

Situative Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mathematik – Entwicklung und Validierung eines Testinstruments - Bruns, Julia; Strahl, Carolin; Gasteiger, Hedwig (Unterrichtswissenschaft)
Zusammenfassung Frühe mathematische Bildung findet in der Kindertagesstätte insbesondere in spontanen Alltagssituationen statt. Damit diese Alltagssituationen zu natürlichen Lernsituationen für die Kinder werden, müssen (angehende) frühpädagogische Fachkräfte zunächst das mathematische Potenzial in diesen Situationen erkennen. Diese Fähigkeit zur situativen Beobachtung und Wahrnehmung ist bisher unzureichend erforscht, was unter anderem auf begrenzte Methoden zur standardisierten Erfassung dieses Konstrukts zurückzuführen ist. Um diesem Bedarf zu begegnen, wurde das videobasierte Testinstrument Vimas_num zur Erfassung der Fähigkeit zur situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mengen und Zahlen entwickelt. Auf der Grundlage von drei aufeinander aufbauenden Studien wird die Validität verschiedener Aspekte der Testwertinterpretation untersucht. Die Ergebnisse geben Hinweise auf die Validität der Testwertinterpretation in Bezug auf den Testinhalt, die interne Struktur des Tests und die Zusammenhänge mit theoretisch verbundenen Konstrukten.
Keywords: Education

Interaktionen in mathematischen Spielsituationen in Kindertagesstätte und Familie - Meyer, Lena; Tabeling, Laura; Gasteiger, Hedwig; Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

Adaptionshandlungen von Multiplikatorinnen und Multiplikatoren zur frühen mathematischen Bildung – Beschreibung und Bewertung aus fachbezogener Perspektive - Bruns, Julia; Schopferer, Theresa; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Die Implementation früher mathematischer Bildung in Kindertagesstätten kann durch fachdidaktische Fortbildungen für frühpädagogische Fachkräfte unterstützt werden. Um Fachkräfte in der Breite zu erreichen, erscheint ein scaling up Ansatz geeignet, bei dem aufbauend auf das Fortbildungskonzept EmMa – Erzieherinnen und Erzieher machen Mathematik Multiplikatorinnen und Multiplikatoren qualifiziert werden. Dabei ergibt sich die Herausforderung, dass Fortbildende im Elementarbereich kaum mathematisches und mathematikdidaktisches Wissen mitbringen. Der Kontext dieser Studie ist der scaling up Prozess der Fortbildung EmMa unter diesen Umständen. Das Erkenntnisinteresse liegt in der Beschreibung und Bewertung der Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren. Für die Bewertung der Adaptionen werden zwei Kriterien herangezogen: (1) das Kriterium der Präzision, das die Vollständigkeit und Klarheit der Inhalte umfasst und (2) das Kriterium der fachlichen Korrektheit, das durch das Ausbleiben fachbezogener Fehler beschrieben wird. Analysiert werden dabei die theoretischen, fachbezogenen Phasen der von Multiplikatorinnen und Multiplikatoren durchgeführten Fortbildung zur frühen mathematischen Bildung, da davon ausgegangen wird, dass insbesondere diese theoretischen Inhalte für diese Gruppe von Multiplikatorinnen und Multiplikatoren eine Herausforderung darstellen. Zur Untersuchung wurde eine videogestützte, qualitative Feldstudie mit N = 8 Fällen durchgeführt. Mit Hilfe der qualitativen Inhaltsanalyse wurden die Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren charakterisiert und hinsichtlich ihrer Präzision und der fachlichen Fehler in diesen Adaptionen analysiert. Dabei zeigte sich, dass der eigenständige Umgang mit den mathematischen und mathematikdidaktischen Inhalten des Fortbildungskonzepts EmMa trotz intensiver Unterstützung anspruchsvoll und bei vielen Multiplikatorinnen und Multiplikatoren mit fachbezogenen Fehlern verbunden ist. Implikationen dieser Ergebnisse für die weitere Forschung werden diskutiert.

Situational Perception in Mathematics (SPiM)—Results of a Cross-Country Study in Austria and Norway - Bruns, Julia; Carlsen, Martin; Eichen, Lars; Erfjord, Ingvald; Hundeland, Per Sigurd (Mathematics Education in the Early Years)

Mathematisches Fachwissen von frühpädagogischen Fachpersonen im Spannungsfeld zwischen Disziplin- und Praxis - Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

“Why don’t you make a drawing?" Motivation and strategy use in mathematical modelling - Schönherr, Johanna; Blomberg, J.; Schukajlow, S.; Rellensmann, J. (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education: PME)

Measuring and investigating strategic knowledge about drawing to solve geometry modelling problems - Schönherr, Johanna; Schukajlow, S.; Leopold, C. (ZDM – Mathematics Education)

Paderborner Qualitätsstern zur Einschätzung der Kooperation im Übergang Kita – Grundschule. Herausgegeben von: Höke, Julia; Büker, Petra, Ogrodowski, Jana & Vollmann, Britta. Unter Mitarbeit von Alina Bruyn und Theresa Driller. Dieses Instrument liegt seit 2021 ebenfalls in vollständiger englischer Übersetzung vor: https://blogs.uni-paderborn.de/pq3-international/ - Herding, Jana

Zur Bedeutung von Integrationserfahrungen in der Grundschulzeit aus der Retroperspektive junger Erwachsener: eine Interviewstudie - Herding, Jana; Ogrodowski, J. (Diversität und soziale Ungleichheit. Herausforderungen an die Integrationsleistung der Grundschule. Jahrbuch Grundschulforschung)

Digitale Transformationsprozesse in der beruflichen Benachteiligtenförderung – erste Ergebnisse einer qualitativen Studie - Schemmer, Susanne Jutta (Digitalisierung am Übergang Schule Beruf. Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf - Schemmer, Susanne Jutta; Heisler, Dietmar (bwp@Berufs-und Wirtschaftspädagogik – online, (24.06.2020))

Semantic-based End-to-End Learning for Typhoon Intensity Prediction - Zahera, H.M.A (Arxiv)

ProBERT: Product Data Classification with Fine-tuning BERT Model. - Zahera, H.M.A; Sherif, Mohamed (MWPD@ ISWC)

On the multi-domain compact finite difference relaxation method for high dimensional chaos: The nine-dimensional Lorenz system - Kouagou, N.J.; Dlamini, P.G.; Simelane, S.M. (Alexandria Engineering Journal)
In this paper, we implement the multidomain compact finite difference method to numerically study high dimensional chaos by considering the nine-dimensional Lorenz system. Most of the existing numerical methods converge slowly for this kind of problems and this results in inaccurate approximations. Though highly accurate, the compact finite difference method becomes less accurate for problems characterized by chaotic solutions, even with an increase in the number of grid points. As a result, in this work, we adopt the multidomain approach. This approach remarkably improves the results as well as the efficiency of the method.
Keywords: Multidomain; Compact finite difference; 9D Lorenz system

Geschlechterverwirrungen. Was wir wissen, was wir glauben und was nicht stimmt
In Geschlechterfragen kann jede*r mitreden – und ist dabei oft von Irrtümern und Vorurteilen geleitet. 32 Autorinnen und Autoren befassen sich in diesem Band mit unserem Wissen, Glauben und Nichtwissen zu Geschlecht und »Gender«. Die Beiträge, die von historischen über philosophische und körperbezogene bis zu politischen Themen reichen, wollen sachkundig informieren, seriös aufklären – und auch ein wenig verwirren, indem sie ihren Gegenstand von unterschiedlichen Seiten betrachten und dabei zeigen, was wir nicht wissen.

Parameterized complexity of abduction in Schaefer’s framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Journal of Logic and Computation)
Abstract Abductive reasoning is a non-monotonic formalism stemming from the work of Peirce. It describes the process of deriving the most plausible explanations of known facts. Considering the positive version, asking for sets of variables as explanations, we study, besides the problem of wether there exists a set of explanations, two explanation size limited variants of this reasoning problem (less than or equal to, and equal to a given size bound). In this paper, we present a thorough two-dimensional classification of these problems: the first dimension is regarding the parameterized complexity under a wealth of different parameterizations, and the second dimension spans through all possible Boolean fragments of these problems in Schaefer’s constraint satisfaction framework with co-clones (T. J. Schaefer. The complexity of satisfiability problems. In Proceedings of the 10th Annual ACM Symposium on Theory of Computing, May 1–3, 1978, San Diego, California, USA, R.J. Lipton, W.A. Burkhard, W.J. Savitch, E.P. Friedman, A.V. Aho eds, pp. 216–226. ACM, 1978). Thereby, we almost complete the parameterized complexity classification program initiated by Fellows et al. (The parameterized complexity of abduction. In Proceedings of the Twenty-Sixth AAAI Conference on Articial Intelligence, July 22–26, 2012, Toronto, Ontario, Canada, J. Homann, B. Selman eds. AAAI Press, 2012), partially building on the results by Nordh and Zanuttini (What makes propositional abduction tractable. Artificial Intelligence, 172, 1245–1284, 2008). In this process, we outline a fine-grained analysis of the inherent parameterized intractability of these problems and pinpoint their FPT parts. As the standard algebraic approach is not applicable to our problems, we develop an alternative method that makes the algebraic tools partially available again.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

Parameterised Complexity of Model Checking and Satisfiability in Propositional Dependence Logic - Mahmood, Yasir; Meier, Arne (Lecture Notes in Computer Science)

DeepWind: An Accurate Wind Turbine Condition Monitoring Framework via Deep Learning on Embedded Platforms - Ghasemzadeh Mohammadi, Hassan; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Kuschel, Maurice; Jentzsch, Felix Paul; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Design and Implementation of a ReconOS-based TensorFlow Lite Delegate Architecture - Jentzsch, Felix P.
Modern machine learning (ML) techniques continue to move into the embedded system space because traditional centralized compute resources do not suit certain application domains, for example in mobile or real-time environments. Google’s TensorFlow Lite (TFLite) framework supports this shift from cloud to edge computing and makes ML inference accessible on resource-constrained devices. While it offers the possibility to partially delegate computation to hardware accelerators, there is no such “delegate” available to utilize the promising characteristics of reconfigurable hardware. This thesis incorporates modern platform FPGAs into TFLite by implementing a modular delegate framework, which allows accelerators within the programmable logic to take over the execution of neural network layers. To facilitate the necessary hardware/software codesign, the FPGA delegate is based on the operating system for reconfigurable computing (ReconOS), whose partial reconfiguration support enables the instantiation of model-tailored accelerator architectures. In the hardware back-end, a streaming-based prototype accelerator for the MobileNet model family showcases the working order of the platform, but falls short of the desired performance. Thus, it indicates the need for further exploration of alternative accelerator designs, which the delegate could automatically synthesize to meet a model’s demands.

Global generalized solutions to a forager–exploiter model with superlinear degradation and their eventual regularity properties - Black, Tobias (Mathematical Models and Methods in Applied Sciences)
Keywords: Applied Mathematics; Modeling and Simulation

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Enhanced electrocatalytic oxygen evolution by manipulation of electron transfer through cobalt-phosphorous bridging - Pan, Ying; Ren, Hangjuan; Chen, Ruizhe; Wu, Yanfang; Chu, Dewei (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar A.; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

An Algorithmic Solution for Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef (the International Journal On Advances in Software)

Zirkel und Lineal ohne Parallelenaxiom: Ein konstruktiver Zugang zur hyperbolischen Geometrie. - Hoffmann, Max (Der Mathematikunterricht)

Die Bedeutung unterschiedlicher Heterogenitätsmerkmale für das Erleben von Zustandsangst vor dem Sportunterricht in der Grundschule - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J. (Grundschulsport. Empirische Einblicke und pädagogische Empfehlungen)

Von Interkultureller Kompetenz und sportpädagogischem Können in postmigrantischen Gesellschaften. Grundlagen und Weiterentwicklung eines Forschungsprogramms - Grimminger-Seidensticker, Elke; Gieß-Stüber, P.; Möhwald, Aiko Julia (Sport im Kontext globaler Zusammenarbeit)

Sportdidaktik - Grimminger-Seidensticker, Elke; Oesterhelt, V.; Gerlach, E.; Friedrich, G. (Lernen im Fach und über das Fach hinaus)

Zum Umgang mit Heterogenität im Sportunterricht - Grimminger-Seidensticker, Elke; Frohn, J. (Empirie des Schulsports)

Machthandlungen von Schüler*innen im Sportunterricht – Welche Rolle spielt das Sportlehrer*innenhandeln? - Grimminger-Seidensticker, Elke (sportunterricht)

Körperbild, Bewegung und Sport in der Wahrnehmung von Grundschulkindern. Ergebnisse einer explorativen lnterviewstudie - Grimminger-Seidensticker, Elke; Korte, J.; Möhwald, Aiko Julia (sportunterricht)

A 14-weeks intervention study on changing preservice teachers’ psychological perspectives related to teaching inclusively: Explicit and implicit attitude, self-efficacy, and stress perception towards inclusion - Grimminger-Seidensticker, Elke; Lautenbach, F.; Heyder, A.; Korte, J.; Möhwald, Aiko Julia (Frontiers in Education)

Quantitative and qualitative results of a body image pilot intervention in (pre)adolescent girls - Grimminger-Seidensticker, Elke; Korte, J. (Journal of Physical Education & Health)

Health concepts among socially disadvantaged children in France, Germany and Switzerland - Grimminger-Seidensticker, Elke; Aceti, Monica; Knobé, Sandrine; Vieille Marchiset, Gilles (Health Promotion International)
Summary As health concepts develop through exposure to, and experience with particular contexts, and as health concepts influence health behaviour, it is important for actors in health promotion programmes to understand an individual’s health concepts. This study focussed on health concepts among socially disadvantaged children in France, Germany, Italy and Switzerland—a hitherto less researched population group. We conducted focus groups with a total of 167 children aged 7–11 years (mean=8.76 years, SD=0.68). The aim of this study was to explore if the life situation across four different countries leads to similar health concepts, and how the particular, national health discourses are reflected in the children’s health concepts. The data were analysed through a structured qualitative content analysis and revealed four categories: ‘Symbols/symptoms of health/illness’, ‘Emotionality’, ‘Healthy/unhealthy practices’, and ‘Consequences of health problems’. The children’s health concepts are linked to concrete events and objects, and they are able to think in logical sequences. However, the children’s causal argumentation is uni-dimensional; they do not cover the complexity of the development of health problems. In particular, overweight stands for illness and is exclusively the result of unhealthy practices. In their concepts, the children reflect the national health promotion programme discourses about overweight. They seem to understand the messages of health education as ‘behaving well means being healthy’; however, such a health education message initiates accusations of ‘unhealthy persons’. In consequence, challenges for sensitive health education programmes (at school) are discussed.

A 14-Week Intervention Study on Changing Preservice Teachers’ Psychological Perspectives on Inclusion: Explicit and Implicit Attitudes, Self-Efficacy, and Stress Perception Toward Inclusion - Lautenbach, Franziska; Korte, Johanna; Möhwald, Aiko; Heyder, Anke; Grimminger-Seidensticker, Elke (Frontiers in Education)

SUBCLINICAL DISORDERED EATING AND BODY DISSATISFACTION IN NORMAL WEIGHT CHILDREN—THE ROLE OF PHYSICAL ACTIVITY AND MOTIVES TO EXERCISE - Grimminger-Seidensticker, Elke; Korte, Johanna; Möhwald, Aiko; Trojan, Jörg (Journal of Physical Education & Health)

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan
Review von Holger Zellentin, Review of Qur'anic Research, Vol. 7 no. 5 (2021) Rezension von Bertram Schmitz, Theologische Literaturzeitung, Nr. 7, 2021, Spalte 657-658 Review von Sebastian Bitsch, Der Islam, Band 98, Heft 2, 2021, 591-598

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (arXiv:2011.06434)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $M$ is a stochastic process that models a random perturbation of the geodesic flow. If $M$ is a orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the $L^2$-spectrum of the infinitesimal generator of a time rescaled version of the process converges to the Laplace spectrum of the base manifold.